Building the optimal portfolio for stock using multi-objective genetic algorithm - comparative analytical research in the Iraqi stock market - اسماعيل, مصطفى منير; غناوي, حيدر عدنان (Journal of Economics and Administrative Sciences, 2019)
Abstract:The main objective of the research is to build an optimal investment portfolio of stocks’ listed at the Iraqi Stock Exchange after employing the multi-objective genetic algorithm within the period of time between 1/1/2006 and 1/6/2018 in the light of closing prices (43) companies after the completion of their data and met the conditions of the inspection, as the literature review has supported the diagnosis of the knowledge gap and the identification of deficiencies in the level of experimentation was the current direction of research was to reflect the aspects of the unseen and untreated by other researchers in particular, the missing data and non-reversed pieces the reality of trading at the level of companies , the financial market and concluded by choosing the most suitable one or employing multiple objective genetic algorithm tool, they are limited either by building portfolios and choose one or generate optimal portfolios without paying attention to the issue of the missing data in the data series or the omission of the possibility of generating investment portfolios and classified it according to the preferences of the investor and other employed genetic algorithm without linking them to objective of portfolio return and risk. After the application of the idea of the ​​research mentioned tools, results of quantitative analysis concluded to build two portfolios the optimal portfolio under original data and the optimal portfolio under the original data improved performance using multiple objective genetic algorithm. The optimal portfolio improved by using multiple objective genetic algorithm achieved the highest level of performance to the degree of superiority on the portfolio of the Iraq market index ; that marks the validity of the combination between objective programming and genetic algorithm to Building an optimal investment portfolio that guarantees the investor in the Iraqi stocks market the right tradeoff  between return and risk, in a manner that positively reflects the achievement of the goal of maximizing his wealth from his limited resources.